The Intelligent Web-Based Tutoring System using the C++ Standard Template Library - Lee, C. (Malaysian Educational Technology Association, 2005)
An intelligent tutoring system (ITS) is a computer-based instructional system with models of instructional contents that specify what to teach and teaching strategies that specify how to teach. Earlier work on creating an ITS for programming focused on the teaching programming syntax as opposed to application. The main teaching strategy is to present problem specifications for students to solve, followed by the intelligent analysis of their solutions. However, this research focused on the application level of learning programming using the C++ standard template library (STL). It has been discovered that students find C++ STL difficult due to their weaknesses in understanding various object-oriented concepts; this understanding forms the prerequisite in learning the application of the STL. As the STL is taught at the second level of a degree course, tutors face difficulties in dealing with various levels of prerequisite skills of each student. Therefore, the ITS overcomes the challenges by modelling programme specifications based on prerequisite concepts. The Bayesian theorem is applied to model the studentâs knowledge and direct the tutoring intelligently. This paper describes the ITS development which applies practices from the eXtreme programming methodology and J2EE technologies. An evaluation of the preliminary system testing is also included. Combining Web technologies and the ITS provides both globalisation and individualisation in teaching and learning.